Sulfur-containing material, sulfur-containing battery material, electrode and battery
By using sulfur-modified compounds and CuKα ray powder X-ray diffraction technology, sulfur-containing materials with a total sulfur content of more than 50 mass % were prepared, which solved the problem of insufficient discharge capacity of sulfur-containing materials in the prior art, and achieved improvement of battery capacity and optimization of cycle characteristics and safety.
Patent Information
- Application Number
- CN202380065747.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-15
- Filing Date
- 2023-09-04
- Publication Date
- 2025-04-22
AI Technical Summary
The sulfur-containing materials used in the prior art are difficult to form battery materials with larger discharge capacity.
The sulfur-containing material containing a sulfur-modified compound has a total sulfur content of more than 50 mass % and the ratio (A/B) between the maximum peak intensity (A) of the diffraction angle (2θ) obtained by powder X-ray diffraction of CuKα rays and the maximum peak intensity (B) of the diffraction angle (2θ) in the range of 23.0° to 23.4° and the maximum peak intensity (B) in the range of 24.8° to 25.2° is 1.5 or less.
The discharge capacity is increased and the cycle characteristics and safety of the battery are improved.
Smart Images

Figure BDA0005309367310000291 
Figure BDA0005309367310000292 
Figure BDA0005309367310000301
Abstract
Description
Technical Field
[0001] The present disclosure relates to a sulfur-containing material, a sulfur-containing battery material, an electrode and a battery. Background Art
[0002] Batteries are used for various purposes. The characteristics of batteries depend on the electrodes, separators, electrolytes, etc., which are its components, and research and development of each component is in full swing. In electrodes, active materials in electrode layers, binders, current collectors, etc. are all important, and research and development is in full swing. As active materials, for example, sulfur-containing materials are known (for example, refer to Patent Documents 1 and 2). Prior art literature
[0003] Patent Literature Patent Document 1: International Publication No. 2010 / 044437 Patent Document 2: Japanese Patent Application Publication No. 2014-022123 Summary of the invention Problems to be solved by the invention
[0004] The sulfur-containing material used in Patent Document 1 and the like is required to be a material capable of forming a battery having a larger discharge capacity.
[0005] The present disclosure has been made in view of the above-mentioned problems, and a main object thereof is to provide a sulfur-containing material whose discharge capacity can be easily increased. Means of solving problems
[0006] The present inventors have conducted intensive studies and have found that a sulfur-containing material containing a sulfur-modified compound, having a specific total sulfur content (total sulfur content), and having a value measured by powder X-ray diffraction using CuKα rays that satisfies a predetermined condition can solve the above-mentioned problems.
[0007] That is, the present disclosure is a sulfur-containing material, characterized in that it contains a sulfur-modified compound, the total sulfur content is 50% by mass or more, and the ratio (A / B) of the maximum peak intensity (A) in the range of a diffraction angle (2θ) of 23.0° to 23.4° to the maximum peak intensity (B) in the range of a diffraction angle (2θ) of 24.8° to 25.2° obtained by powder X-ray diffraction using CuKα rays is 1.5 or less (A / B≤1.5).
[0008] In the sulfur-containing material disclosed herein, it is preferred that the sulfur-modified compound be a sulfur-modified acrylic compound.
[0009] The present invention discloses a sulfur-containing battery material, characterized in that it contains a sulfur-modified compound, the total sulfur content is 50% by mass or more, and the ratio (A / B) of the maximum peak intensity (A) in the range of a diffraction angle (2θ) of 23.0° to 23.4° and the maximum peak intensity (B) in the range of a diffraction angle (2θ) of 24.8° to 25.2° obtained by powder X-ray diffraction using CuKα rays is 1.5 or less (A / B≤1.5).
[0010] In the sulfur-containing battery material disclosed herein, the sulfur-modified compound is preferably a sulfur-modified acrylic compound.
[0011] The present disclosure is an electrode having an electrode layer including the above-mentioned sulfur-containing material.
[0012] The present disclosure is a battery having the above-mentioned electrode.
[0013] In the battery disclosed herein, the electrode is preferably a positive electrode.
[0014] The negative electrode of the battery of the present disclosure is preferably lithium. Effects of the Invention
[0015] According to the present disclosure, it is possible to provide a sulfur-containing material whose discharge capacity is easily increased. BRIEF DESCRIPTION OF THE DRAWINGS Figure 1 is an example of the Raman spectrum of sulfur-containing material A. Figure 2 This is the measurement result of the sulfur-containing material A by powder X-ray diffraction. Figure 3 It is the measurement result of powder X-ray diffraction of sulfur-containing material b. DETAILED DESCRIPTION
[0017] The sulfur-containing material, sulfur-containing battery material, electrode and battery of the present disclosure are described in detail.
[0018] A. Sulfur-containing materials First, the sulfur-containing material of the present disclosure will be described. The sulfur-containing material disclosed herein contains a sulfur-modified compound, wherein the total sulfur content is 50% by mass or more, and the ratio (A / B) of the maximum peak intensity (A) in the range of a diffraction angle (2θ) of 23.0° to 23.4° to the maximum peak intensity (B) in the range of a diffraction angle (2θ) of 24.8° to 25.2° obtained by powder X-ray diffraction using CuKα rays is 1.5 or less (A / B≤1.5).
[0019] The sulfur-containing material of the present disclosure contains at least a sulfur-modified compound. That is, the sulfur-containing material may contain, for example, a sulfur-modified compound, elemental sulfur, and impurities. In the present disclosure, elemental sulfur may be sulfur that does not form a stable interaction with a sulfur-modified compound. Specifically, elemental sulfur is not particularly limited, and examples thereof include α-sulfur, β-sulfur, and γ-sulfur having an S8 structure.
[0020] According to the present disclosure, by using the above sulfur-containing material in a battery, the discharge capacity is increased, and even if the charge and discharge are repeated, the discharge capacity is not easily reduced, that is, the cycle characteristics are improved. In addition, the sulfur-containing material of the present disclosure has excellent flame retardancy, so the safety of the battery can be improved.
[0021] The reason why such an effect is produced by using the sulfur-containing material of the present disclosure is not clear, but is presumed as follows. When the total content of sulfur, which has a theoretical capacity of about 1670 mAh / g, is 50 mass % or more, the discharge capacity increases. In addition, by satisfying a predetermined peak intensity relationship obtained by powder X-ray diffraction, it is estimated that the proportion of organic sulfur in the sulfur contained in the sulfur-containing material is large. Here, organic sulfur is different from elemental sulfur, and may be, for example, sulfur that forms a stable interaction in a sulfur-modified compound or sulfur that forms a stable interaction with a sulfur-modified compound. As a result of such a large proportion of organic sulfur, for example, during charge and discharge, the reactivity of sulfur and lithium can be improved, thereby suppressing the dissolution and side reactions of lithium polysulfide, effectively increasing the discharge capacity, and achieving the effect of improving the cycle characteristics. Furthermore, since the proportion of elemental sulfur in the sulfur contained in the sulfur-containing material is small, it can simultaneously exert the effects of suppressing flammability and improving battery safety. The organic sulfur may be composed of a single sulfur atom that forms a stable interaction, or may be a plurality of sulfur atoms such as disulfide, trisulfide, etc. When there are a plurality of sulfur atoms, some of the sulfur atoms may interact with each other. For example, in the case of a linear sulfur, at least one terminal sulfur may form a stable interaction. In addition, as a stable interaction, the following can be cited: in powder X-ray diffraction using CuKα rays, no diffraction peak due to elemental sulfur is generated, more specifically, no strong diffraction peak is generated at a diffraction angle (2θ) such as around 23.2° (for example, in the range of 23.0° to 23.4°), for example, covalent bonds or ionic bonds, etc. can be cited.
[0022] 1. Diffraction peak The sulfur-containing material disclosed in the present invention satisfies the following relationship: the ratio (A / B) of the maximum peak intensity (A) in the range of a diffraction angle (2θ) of 23.0° to 23.4° to the maximum peak intensity (B) in the range of a diffraction angle (2θ) of 24.8° to 25.2° obtained by powder X-ray diffraction using CuKα rays is 1.5 or less (A / B≤1.5).
[0023] In the present disclosure, powder X-ray diffraction using CuKα rays may be any analytical method for obtaining information related to the structure and phase identification of a crystalline substance. The measurement is not particularly limited, and an example thereof is Ultima IV manufactured by RIKEN Co., Ltd. (voltage: 40 kV, current: 40 mA, scanning speed: 0.5° / min, sampling: 0.02°, cumulative number of times: 1, diffraction angle (2θ): 10° to 40°).
[0024] In the present disclosure, "the maximum peak intensity (A) in the range of diffraction angle (2θ) of 23.0° to 23.4°" means the difference between the maximum value I(A-max) of the diffraction intensity (cps) measured in the range of 23.0° to 23.4° and the minimum value I(min) of the diffraction intensity (cps) measured in the range of 20.0° to 40.0°. That is, (A) = I(A-max) - I(min). In addition, "the maximum peak intensity (B) in the range of diffraction angle (2θ) of 24.8° to 25.2°" means the difference between the maximum value I(B-max) of the diffraction intensity (cps) measured in the range of 24.8° to 25.2° and the minimum value I(min) of the diffraction intensity (cps) measured in the range of 20.0° to 40.0°. That is, (B) = I(B-max) - I(min).
[0025] In the present disclosure, from the viewpoint of increasing the discharge capacity while improving the cycle characteristics and further improving the battery safety, the peak intensity ratio (A / B) is preferably 1.4 or less (A / B≤1.4), more preferably 1.2 or less (A / B≤1.2), and even more preferably 1.0 or less (A / B≤1.0).
[0026] In the present disclosure, as a method for adjusting the peak intensity ratio (A / B), for example, a method of adjusting the conditions of each process of the method for producing a sulfur-containing material described later can be cited. In particular, as the above-mentioned production method, a method having a mechanochemical treatment process in addition to a heating process is used, and the conditions of the mechanochemical treatment in the above-mentioned mechanochemical treatment process are adjusted, or the content of elemental sulfur in the heat-treated product that is the object of the mechanochemical treatment is adjusted. Specifically, the peak intensity ratio (A / B) can be reduced by extending the treatment time, increasing the rotation speed of the planetary ball mill used for the mechanochemical treatment, or implementing both.
[0027] 2. Total sulfur content The total sulfur content of the sulfur-containing material of the present disclosure is 50% by mass or more. Here, "total sulfur content" refers to the total content of sulfur atoms. The total sulfur content in the sulfur-containing material can be calculated based on the analysis results using a CHNS analysis device that can analyze sulfur and oxygen.
[0028] From the viewpoint of further increasing the discharge capacity, the total content of sulfur in the sulfur-containing material of the present disclosure is preferably 50% by mass to 90% by mass, preferably 51% by mass to 85% by mass, more preferably 52% by mass to 80% by mass, further preferably 53% by mass to 75% by mass, further preferably 53% by mass to 70% by mass, and most preferably 55% by mass to 70% by mass.
[0029] 3. Sulfur-modified compounds As the sulfur-modified compound used in the sulfur-containing material of the present disclosure, for example, a compound in which sulfur is covalently bonded to atoms in an organic compound can be used. As a method for producing such a sulfur-modified compound, there is a method of heating elemental sulfur and an organic compound.
[0030] Examples of the organic compound include acrylic compounds, polyether compounds, asphalt compounds, polynuclear aromatic ring compounds, aliphatic hydrocarbon compounds, and thienoacene compounds. That is, examples of the sulfur-modified compound include sulfur-modified acrylic compounds, sulfur-modified polyether compounds, sulfur-modified asphalt compounds, sulfur-modified polynuclear aromatic ring compounds, sulfur-modified aliphatic hydrocarbon compounds, polythienoacene compounds, polycarbon sulfide, and the like.
[0031] In the present disclosure, from the viewpoint of further increasing the discharge capacity and further improving the safety of the battery, the sulfur-modified compound is preferably selected from sulfur-modified acrylic compounds, sulfur-modified polynuclear aromatic ring compounds and sulfur-modified polyether compounds, and more preferably sulfur-modified acrylic compounds.
[0032] The total sulfur content in the sulfur-modified compound is not particularly limited, but from the viewpoint of further increasing the discharge capacity, it is preferably 30% to 80% by mass, more preferably 40% to 75% by mass, and most preferably 45% to 70% by mass. Here, the total sulfur content in the sulfur-modified compound can be calculated based on the analysis results using a CHNS analyzer that can analyze sulfur and oxygen.
[0033] In the present disclosure, from the viewpoint of increasing the discharge capacity and reducing the flammability to improve the safety, the sulfur-modified compound is preferably contained at 70 parts by mass or more, more preferably at 75 parts by mass or more, further preferably at 80 parts by mass or more, further preferably at 90 parts by mass or more, further preferably at 95 parts by mass or more, and further preferably at 98 parts by mass or more, relative to 100 parts by mass of the sulfur-containing material.
[0034] In the present disclosure, the content of the sulfur-modified compound can be measured by a known method. For example, the content of the sulfur-modified compound can be measured by thermogravimetric analysis of the sulfur-containing material. In the thermogravimetric analysis method, under the conditions of a heating start temperature of 100°C or less and a heating rate of 10°C / min, the thermal weight loss maintenance rate is measured until reaching 350°C, and the content ratio (mass %) of the residual substance is confirmed, thereby determining the content of the sulfur-modified compound in the sulfur-containing material.
[0035] (1) Sulfur-modified acrylic compounds As the sulfur-modified acrylic compound used in the sulfur-containing material of the present disclosure, for example, a compound in which sulfur is covalently bonded to atoms in an acrylic compound can be used. As a method for producing such a sulfur-modified acrylic compound, there is a method of heating elemental sulfur and an acrylic compound.
[0036] In the present disclosure, examples of acrylic compounds include polyacrylonitrile compounds and other acrylic compounds.
[0037] In the present disclosure, examples of the sulfur-modified acrylic compound include sulfur-modified polyacrylonitrile compounds and other sulfur-modified acrylic compounds. From the viewpoint of increasing the discharge capacity, the sulfur-modified acrylic compound is preferably a sulfur-modified polyacrylonitrile compound.
[0038] The total sulfur content in the sulfur-modified acrylic compound is not particularly limited, but is preferably 30% to 80% by mass, more preferably 40% to 75% by mass, and most preferably 45% to 70% by mass from the viewpoint of further increasing the discharge capacity. Here, the total sulfur content in the sulfur-modified acrylic compound can be calculated based on the analysis results using a CHNS analyzer that can analyze sulfur and oxygen.
[0039] (1-1) Sulfur-modified polyacrylonitrile compounds The sulfur-modified polyacrylonitrile compound disclosed in the present invention may be, for example, a compound in which sulfur is covalently bonded to atoms in a polyacrylonitrile compound. As a method for producing such a sulfur-modified polyacrylonitrile compound, a method of heating elemental sulfur and a polyacrylonitrile compound may be cited. In addition, the sulfur-modified polyacrylonitrile compound disclosed in the present invention may also include a compound obtained by heating particles containing hydrocarbons in an outer shell composed of a polyacrylonitrile compound and elemental sulfur. The hydrocarbon contained may be a saturated or unsaturated aliphatic hydrocarbon having 3 to 8 carbon atoms.
[0040] In the present disclosure, the polyacrylonitrile compound may contain a structural unit derived from at least one of acrylonitrile and methacrylonitrile. From the viewpoint of increasing the discharge capacity, the polyacrylonitrile compound preferably contains at least a structural unit derived from acrylonitrile.
[0041] From the viewpoint of increasing the discharge capacity, the content of the structural unit derived from acrylonitrile and methacrylonitrile is preferably 10 parts by mass or more, more preferably 30 parts by mass or more, in 100 parts by mass of the polyacrylonitrile-based compound.
[0042] In the case where the polyacrylonitrile compound contains a structural unit derived from acrylonitrile, from the viewpoint of increasing the discharge capacity, the content of the structural unit derived from acrylonitrile is preferably 10 parts by mass or more, more preferably 30 parts by mass or more, further preferably 50 parts by mass or more, further preferably 80 parts by mass or more, further preferably 85 parts by mass or more, further preferably 90 parts by mass or more, further preferably 95 parts by mass or more, and most preferably 100 parts by mass, that is, it is most preferred that the polyacrylonitrile compound consists only of structural units derived from acrylonitrile.
[0043] When the polyacrylonitrile compound contains a structural unit derived from methacrylonitrile, from the viewpoint of increasing the discharge capacity, the content of the structural unit derived from methacrylonitrile is preferably 10 parts by mass or more in 100 parts by mass of the polyacrylonitrile compound, and is preferably 30 parts by mass or more, and is particularly preferably 30 parts by mass or more and 95 parts by mass or less, and is particularly preferably 30 parts by mass or more and 90 parts by mass or less, and is particularly preferably 30 parts by mass or more and 85 parts by mass or less, and is particularly preferably 30 parts by mass or more and 80 parts by mass or less.
[0044] The polyacrylonitrile compound may contain structural units derived from other monomers other than acrylonitrile and methacrylonitrile. Examples of other monomers include acrylic monomers such as (meth)acrylate, (meth)acrylate, (meth)acrylamide, ethylene glycol (meth)acrylate, 1,6-hexanediol (meth)acrylate, neopentyl glycol di(meth)acrylate, and glycerol di(meth)acrylate; and conjugated dienes such as butadiene and isoprene. Two or more of these other monomers may be used in combination. Here, "(meth)acrylate" means any of "acrylate" and "methacrylate." "(Meth)acrylic acid" means any of "acrylic acid" and "methacrylic acid."
[0045] When the sulfur-modified material of the present invention contains a sulfur-modified polyacrylonitrile compound which is preferably a sulfur-modified compound, the Raman spectrum of the sulfur-containing material of the present invention may be any as long as the sulfur-containing material of the present invention can exert the desired effect. However, from the viewpoint of increasing the discharge capacity, it is preferred that the Raman shift of 1327 cm -1 ±10cm -1From the viewpoint of increasing the discharge capacity, the Raman spectrum of the sulfur-containing material has a peak in the range of 1327 cm -1 ±10cm -1 Outside the range of 1531cm -1 ±10cm -1 Within the range of 939cm -1 ±10cm -1 Within the range of 479cm -1 ±10cm -1 Within the range of 377cm -1 ±10cm -1 Within the range of 318cm -1 ±10cm -1 There is a peak in at least one of the ranges of 1531 cm -1 ±10cm -1 Within the range of 939cm -1 ±10cm -1 Within the range of 479cm -1 ±10cm -1 Within range, 377cm -1 ±10cm -1 Within range and 318cm -1 ±10cm -1 There are peaks in at least two ranges of the range of 1531 cm -1 ±10cm -1 Within range, 939cm -1 ±10cm -1 Within the range of 479cm -1 ±10cm -1 Within the range of 377cm -1 ±10cm -1 Within the range of 318cm -1 ±10cm -1 All of these ranges have peaks within the range.
[0046] From the viewpoint of increasing the discharge capacity, the Raman spectrum of the sulfur-containing material is 1327 cm -1 ±10cm -1 The peak intensity A1 (1327 cm -1 ±10cm -1 The maximum peak in the range is 300cm -1 ~1800cm -1 The difference between the smallest peak in the range) and 1531cm -1 ±10cm -1 The peak intensity in the range B1 (1531cm-1 ±10cm -1 The maximum peak in the range is 300cm -1 ~1800cm -1 The ratio (A1 / B1) of the difference between the minimum peaks in the range (A1 / B1) is preferably 0.30 to 5.0, more preferably 0.50 to 4.5, further preferably 0.70 to 4.0, and most preferably 0.80 to 3.5.
[0047] The Raman spectrum can be obtained by using NRS-3100 manufactured by JASCO Corporation (excitation wavelength λ = 532 nm, grating: 600 l / mm, resolution: 1 cm -1 , exposure time: 30 seconds, slit width: φ50μm) was measured.
[0048] (1-2) Other sulfur-modified acrylic compounds In the present disclosure, the method for producing other sulfur-modified acrylic compounds includes a method of heating a homopolymer or copolymer of elemental sulfur and other acrylic monomers, wherein the other acrylic monomers do not contain a structural unit derived from acrylonitrile or methacrylonitrile. As other acrylic monomers, the same monomers as those described in the above-mentioned "(1-1) Sulfur-modified polyacrylonitrile compounds" can be used.
[0049] (2) Sulfur-modified polynuclear aromatic compounds The sulfur-modified polynuclear aromatic ring compound can be, for example, a compound in which sulfur is covalently bonded to atoms in the polynuclear aromatic ring compound. The sulfur-modified polynuclear aromatic ring compound can be produced, for example, by heating a mixture of elemental sulfur and a polynuclear aromatic ring compound as an organic compound. Examples of polynuclear aromatic ring compounds include naphthalene, anthracene, tetracene, pentacene, phenanthrene, Benzene-based aromatic ring compounds such as pyrene, benzopyrene, perylene, and coronene, aromatic ring compounds in which a part of the benzene-based aromatic ring compounds is a 5-membered ring, or heteroaromatic ring compounds containing heteroatoms in which a part of these carbon atoms is substituted by sulfur, oxygen, nitrogen, etc. In addition, these polynuclear aromatic ring compounds may have a substituent such as a chain or branched alkyl group having 1 to 12 carbon atoms, an alkoxy group, a hydroxyl group, a carboxyl group, an amino group, an aminocarbonyl group, an aminothio group, a mercaptothiocarbonylamino group, a carboxylalkylcarbonyl group, etc.
[0050] (3) Sulfur-modified polyether compounds As the sulfur-modified polyether compound, the same compounds as those described in JP-A-2022-65974 can be used.
[0051] 4. Sulfur-containing materials In the present disclosure, the method for producing a sulfur-containing material is not particularly limited as long as it is a method that can obtain a material containing a sulfur-modified compound, having a total sulfur content of 50% by mass or more, and satisfying the relationship that the peak intensity ratio (A / B) measured by powder X-ray diffraction is 1.5 or less, and examples thereof include a method having a heating step of heating a mixture of elemental sulfur and an organic compound. The above-mentioned production method may also be a method having a mechanochemical treatment step of subjecting the heat-treated product after the above-mentioned heating step to a mechanochemical treatment.
[0052] The heating step in the above-mentioned production method is a step of heating the mixture of elemental sulfur and the organic compound. From the viewpoint of increasing the discharge capacity and improving the battery safety, in the above-mentioned heating step, the heating temperature is preferably 200 to 600° C., more preferably 250 to 500° C., in a non-oxidizing atmosphere.
[0053] The mechanochemical treatment in the above-mentioned mechanochemical treatment step refers to a treatment that uses high energy locally generated by mechanical energy such as friction and compression during the pulverization process of the solid material to produce a chemical reaction. From the viewpoint of easily adjusting the total sulfur content and adjusting the peak intensity ratio (A / B), the above-mentioned manufacturing method preferably has a mechanochemical treatment step. It is speculated that the above-mentioned mechanochemical treatment easily increases the proportion of organic sulfur in the sulfur contained in the sulfur-containing material. More specifically, it is speculated that the above-mentioned mechanochemical treatment can cause the elemental sulfur contained in the heat-treated product (e.g., elemental sulfur that has not reacted in the heating step) to react with the sulfur-modified compound, resulting in an easy increase in the proportion of organic sulfur.
[0054] The above-mentioned mechanochemical treatment can, for example, cause mechanical energy such as impact, friction, compression, shearing to act on the heat-treated object, or cause these to act in combination. As an apparatus for performing the mechanochemical treatment, a known apparatus can be used, for example, a mixing apparatus such as a ball mill, a vibration mill, a planetary ball mill, a cyclone mill, a medium stirring mill, a pulverizer such as a ball medium mill, a roller mill, a mortar, etc., and a jet mill that mainly acts on the heat-treated object with forces such as impact and grinding.
[0055] In the present disclosure, from the viewpoint of further increasing the discharge capacity, the above-mentioned device is preferably a mixing device such as a ball mill, a vibration mill, a planetary ball mill, a cyclone mill, a medium stirring mill, or a pulverizer such as a ball medium mill, a roller mill, or a mortar, and more preferably a mixing device such as a ball mill, a vibration mill, a planetary ball mill, a medium stirring mill, or the like, and further preferably a ball mill, a vibration mill, a planetary ball mill, or a cyclone mill.
[0056] The environment for the mechanochemical treatment may be an oxidizing atmosphere or a non-oxidizing atmosphere, preferably a non-oxidizing atmosphere. An oxidizing atmosphere refers to an atmosphere containing an oxidizing gas, such as an atmosphere containing oxygen, ozone or nitrogen dioxide. A non-oxidizing atmosphere refers to an atmosphere not containing an oxidizing gas, such as an atmosphere composed of nitrogen or argon.
[0057] In the present disclosure, from the viewpoint of increasing discharge capacity and improving battery safety, the environment for performing the mechanochemical treatment is preferably a non-oxidizing atmosphere consisting of nitrogen or argon, and more preferably a non-oxidizing atmosphere consisting of nitrogen.
[0058] The manufacturing method may also include other steps in addition to the heating step and the mechanochemical treatment step. Examples of the other steps include a sulfur content adjustment step performed between the heating step and the mechanochemical treatment step to adjust the elemental sulfur content of the heat-treated product obtained in the heating step.
[0059] As the sulfur content adjustment step, elemental sulfur may be added to the heat-treated product to increase the total sulfur content in the heat-treated product used in the mechanochemical treatment step, or elemental sulfur may be removed from the heat-treated product to reduce the elemental sulfur content in the heat-treated product used in the mechanochemical treatment step.
[0060] B. Sulfur-containing battery materials Next, the sulfur-containing battery material of the present disclosure will be described. The sulfur-containing battery material disclosed herein contains a sulfur-modified compound, wherein the total sulfur content is 50% by mass or more, and the ratio (A / B) of the maximum peak intensity (A) in the range of a diffraction angle (2θ) of 23.0° to 23.4° to the maximum peak intensity (B) in the range of a diffraction angle (2θ) of 24.8° to 25.2° obtained by powder X-ray diffraction using CuKα rays is 1.5 or less (A / B≤1.5).
[0061] According to the present disclosure, by using the above-mentioned sulfur-containing battery material in a battery, the discharge capacity is increased. In addition, the above-mentioned sulfur-containing battery material has excellent flame retardancy, so the safety of the battery can be improved.
[0062] In addition, the contents of the sulfur-modified compound, the total sulfur content, and the diffraction peak are the same as those described in the above-mentioned section "A. Sulfur-containing material", and thus the description here is omitted.
[0063] The use of the sulfur-containing battery material disclosed in the present invention is not particularly limited, and it can be used in an electrode layer of an electrode in a battery, and is particularly useful as an active material for an electrode layer.
[0064] In the present disclosure, when the above-mentioned sulfur-containing battery material is an active material of an electrode layer in a battery, from the viewpoint of increasing the discharge capacity, the above-mentioned sulfur-containing battery material is preferably an active material contained in an electrode layer used in a secondary battery, and more preferably an active material contained in a positive electrode active material layer used in a secondary battery, that is, a positive electrode active material. In addition, the battery and the electrode layer in the present disclosure are described in the following "C. Electrode" and "D. Battery".
[0065] C. Electrode The electrode disclosed in the present invention has an electrode layer, and the electrode layer contains the sulfur-containing material described in the above section "A. Sulfur-containing material".
[0066] According to the present disclosure, by using the above-mentioned electrode in a battery, the discharge capacity is increased and the safety of the battery can be improved.
[0067] 1. Electrode layer In the present disclosure, the "electrode layer" includes the above-mentioned sulfur-containing material or the above-mentioned sulfur-containing battery material. In addition, in this specification, the electrode layer when the above-mentioned electrode is a positive electrode is sometimes described as a "positive electrode active material layer", and in addition, the electrode layer when the above-mentioned electrode is a negative electrode is sometimes described as a "negative electrode active material layer". The thickness of the electrode layer is usually 1 μm to 1000 μm.
[0068] In the present disclosure, from the viewpoint of effectively functioning as an active material, increasing the discharge capacity, and improving the safety of the battery, the content of the sulfur-containing material or the sulfur-containing battery material in 100 parts by mass of the electrode layer is preferably 75 parts by mass to 99.5 parts by mass, more preferably 80 parts by mass to 99 parts by mass, and further preferably 85 parts by mass to 98 parts by mass.
[0069] The electrode layer contains a sulfur-containing material or a sulfur-containing battery material, and may contain other components as necessary. When the electrode layer is used as a positive electrode active material layer, other components include a binder and a conductive aid, and may contain an active material other than the sulfur-containing material and the sulfur-containing battery material, a viscosity modifier, a reinforcing material, an antioxidant, etc. as necessary. When the electrode layer is used as a negative electrode active material layer, other components include a binder and a conductive aid, and may contain an active material other than the sulfur-containing material and the sulfur-containing battery material, a viscosity modifier, a reinforcing material, an antioxidant, etc. as necessary.
[0070] As the above-mentioned adhesive, an adhesive known as an adhesive for the electrode layer can be used. As an adhesive, it can be enumerated: styrene-butadiene rubber, butadiene rubber, polyethylene, polypropylene, polyamide, polyamide-imide, polyimide, polyacrylonitrile, polyurethane, polyvinylidene fluoride, polytetrafluoroethylene, ethylene-propylene-diene rubber, fluororubber, styrene-acrylate copolymer, ethylene-vinyl alcohol copolymer, acrylonitrile-butadiene rubber, styrene-isoprene rubber, polymethyl methacrylate, polyacrylate, polyvinyl alcohol, polyvinyl ether, carboxymethyl cellulose, sodium carboxymethyl cellulose, methyl cellulose, cellulose nanofiber, polyethylene oxide, starch, polyvinyl pyrrolidone, polyvinyl chloride, polyacrylic acid, etc. The adhesive can be used only one or in combination of two or more. Among them, from the viewpoint of low environmental load and excellent adhesion, preferably water-based adhesives, more preferably styrene-butadiene rubber, sodium carboxymethyl cellulose and polyacrylic acid.
[0071] From the viewpoint of further increasing the discharge capacity, the content of the binder in the electrode layer is preferably 1 to 30 parts by mass, more preferably 1 to 20 parts by mass, based on 100 parts by mass of the sulfur-containing material or sulfur-containing battery material in the electrode layer.
[0072] As the above-mentioned conductive aid, a conductive aid known as a conductive aid for the electrode layer can be used. Examples of conductive aids include: carbon materials such as natural graphite, artificial graphite, carbon black, Ketjen black, acetylene black, channel black, furnace black, lamp black, thermal black, carbon nanotubes, vapor grown carbon fiber (Vapor Grown Carbon Fiber: VGCF), graphene, fullerene, and needle coke; metal powders such as aluminum powder, nickel powder, and titanium powder; conductive metal oxides such as zinc oxide and titanium oxide; sulfides such as La2S3, Sm2S3, Ce2S3, and TiS2. The conductive aid can be used alone or in combination of two or more.
[0073] From the viewpoint of increasing the discharge capacity, the average particle size of the conductive auxiliary agent is preferably 0.0001 μm to 100 μm, and more preferably 0.01 μm to 50 μm. In the present disclosure, "average particle size" refers to the 50% particle size measured by the laser diffraction light scattering method. In the laser diffraction light scattering method, the particle size is a volume-based diameter, and the secondary particle size of the measured object is measured. When the average particle size is measured by the laser diffraction light scattering method, the measured object is dispersed in a dispersion medium such as water for measurement.
[0074] From the viewpoint of increasing the discharge capacity, the content of the conductive aid in the electrode layer is preferably 0.1 to 50 parts by mass, more preferably 0.5 to 20 parts by mass, further preferably 1.0 to 10 parts by mass, and most preferably 2.0 to 8.0 parts by mass, relative to 100 parts by mass of the sulfur-containing material or sulfur-containing battery material in the electrode layer.
[0075] As active materials other than the above-mentioned sulfur-containing materials and sulfur-containing battery materials (hereinafter sometimes referred to as “other active materials”), known materials as active materials can be used, for example, positive electrode active materials and negative electrode active materials described in “D. Battery” described later.
[0076] As the above-mentioned viscosity modifier, a viscosity modifier known as a viscosity modifier for the electrode layer can be used. Examples of viscosity modifiers include: cellulose polymers such as carboxymethyl cellulose, methyl cellulose, hydroxypropyl cellulose, and their ammonium salts and alkali metal salts; (modified) poly (meth) acrylic acid and their ammonium salts and alkali metal salts; (modified) polyvinyl alcohol, copolymers of acrylic acid or acrylic acid salts and vinyl alcohol, copolymers of maleic anhydride or maleic acid or fumaric acid and vinyl alcohol, and other polyvinyl alcohols; polyethylene glycol, polyethylene oxide, polyvinyl pyrrolidone, modified polyacrylic acid, oxidized starch, starch phosphate, casein, various modified starches, cellulose nanofibers, acrylonitrile-butadiene copolymer hydrogenates, etc. It should be noted that they can also be used as dispersants.
[0077] As the reinforcing material, a known reinforcing material as a reinforcing material for an electrode layer can be used. Examples of the reinforcing material include various inorganic and organic spherical, plate-shaped, rod-shaped or fibrous fillers.
[0078] As the antioxidant, any known antioxidant for an electrode layer can be used. Examples of the antioxidant include phenol compounds, hydroquinone compounds, organic phosphorus compounds, sulfur compounds, phenylenediamine compounds, polymer-type phenol compounds, and the like.
[0079] The method for forming the electrode layer may be any method as long as it is capable of forming the electrode layer, and examples thereof include a method in which an electrode layer-forming composition containing the sulfur-containing material or sulfur-containing battery material, other components as required, and a solvent are applied, and then the solvent is removed from the coating film by drying.
[0080] Examples of the solvent include propylene carbonate, ethylene carbonate, diethyl carbonate, dimethyl carbonate, ethyl methyl carbonate, 1,2-dimethoxyethane, 1,2-diethoxyethane, acetonitrile, propionitrile, tetrahydrofuran, 2-methyltetrahydrofuran, dimethoxyethane, 1,2-dimeth ... Alkane, 1,3-dioxolane, nitromethane, N-methylpyrrolidone, N,N-dimethylformamide, dimethylacetamide, methyl ethyl ketone, cyclohexanone, methyl acetate, methyl acrylate, diethyltriamine, N,N-dimethylaminopropylamine, polyethylene oxide, tetrahydrofuran, dimethyl sulfoxide, cyclopentane, γ-butyrolactone, water, alcohol, etc. The amount of the solvent used can be adjusted according to the coating method. For example, in the case of the doctor blade method, from the perspective of easy manufacturing, the amount of the solvent used is preferably 20 to 300 parts by mass, and more preferably 30 to 200 parts by mass, relative to 100 parts by mass of the total amount of the sulfur-containing material or sulfur-containing battery material, the binder and the conductive aid. The electrode layer forming composition may contain other components other than those described above. Examples of other components include a viscosity modifier, a reinforcing material, and an antioxidant.
[0081] There are no particular restrictions on the method for preparing the electrode layer-forming composition, and examples thereof include a conventional ball mill, sand mill, bead mill, pigment disperser, grinding stirrer, ultrasonic disperser, homogenizer, rotation / revolution mixer, planetary mixer, etc. method.
[0082] As coating method, there is no particular limitation, and various methods such as die coating, comma coating, curtain coating, spray coating, gravure coating, flexographic coating, knife coating, scraper coating, reverse roll coating, brush coating, dip coating can be used. From the viewpoint of being able to obtain a good coating surface state according to the physical properties such as viscosity and dryness of the electrode layer forming composition, die coating, scraper coating, knife coating, comma coating are preferred.
[0083] The drying and removing method is not particularly limited, and heating, decompression, and a combination thereof can be used. The heating temperature can be set to 40° C. to 200° C. The heating and decompression apparatus can be a heating furnace, an infrared heating furnace, a vacuum oven, etc.
[0084] By drying, volatile components such as the solvent are volatilized to form an electrode layer. The electrode layer may then be pressed as required. Examples of the pressing method include a mold pressing method and a roll pressing method.
[0085] 2. Electrodes The electrode disclosed in the present invention has the above-mentioned electrode layer, and may have other structures as required. As other structures, a current collector can be mentioned.
[0086] As the above-mentioned current collector, conductive materials such as titanium, titanium alloy, aluminum, aluminum alloy, copper, nickel, stainless steel, nickel-plated steel, and conductive resin can be used. The surfaces of these conductive materials can be coated with carbon. As the shape of the current collector, foil, plate, mesh, porous, etc. can be cited. Among them, from the viewpoint of conductivity and price, aluminum is preferred, and aluminum foil is more preferred. In the case where the current collector is in the form of foil, from the viewpoint of further increasing the discharge capacity and easy manufacturing, its thickness is usually 1 μm to 100 μm.
[0087] The use of the electrode disclosed in the present invention is not particularly limited, and batteries can be cited. As batteries, for example, primary batteries and secondary batteries can be cited. As secondary batteries, for example, lithium ion secondary batteries, sodium ion secondary batteries, potassium ion secondary batteries, magnesium ion secondary batteries, calcium ion secondary batteries, and aluminum ion secondary batteries can be cited. That is, it can be a lithium sulfur secondary battery, a sodium sulfur secondary battery, a potassium sulfur secondary battery, a magnesium sulfur secondary battery, a calcium sulfur secondary battery, and an aluminum sulfur secondary battery.
[0088] As the use of the electrode disclosed in the present invention, from the perspective of practicality, it is preferably an electrode of a secondary battery, and more preferably an electrode of a lithium ion secondary battery. The electrode disclosed in the present invention can be used as either a positive electrode or a negative electrode, and is preferably used as a positive electrode from the perspective of further increasing the discharge capacity and being easy to manufacture.
[0089] It should be noted that when the above-mentioned electrode is used as an electrode of a lithium ion secondary battery, a pre-doping treatment of inserting lithium can be performed in advance. As a method for pre-doping lithium, it can be based on a known method, for example, the following methods can be cited: an electrolytic doping method in which a half-cell is assembled using metallic lithium as a counter electrode and lithium is electrochemically doped; a diffusion doping method in which a metallic lithium foil is attached to an electrode and placed in a liquid electrolyte and lithium is doped by diffusion of lithium into the electrode, etc.
[0090] When the electrode is used as an electrode of a sodium ion secondary battery, a pre-doping treatment for inserting sodium may be performed in advance. The pre-doping method for sodium may be based on a known method, and for example, the above-mentioned doping method may be used.
[0091] In the present disclosure, the electrode may be subjected to a pressing process as required. Examples of the pressing process include a die pressing method and a roll pressing method.
[0092] D.Battery 1. Electrodes The battery of the present disclosure has the electrodes described in the above-mentioned section "C. Electrode", but may have other structures as necessary.
[0093] According to the battery of the present disclosure, the discharge capacity is increased, the cycle characteristics are improved, and the safety is also improved.
[0094] 2. Other structures Examples of other structures include a counter electrode used in pair with the above-mentioned electrode, an electrolyte, and a separator.
[0095] (1) Counter electrode The counter electrode is an electrode used in pair with the electrode. When the electrode is a positive electrode, the counter electrode is a negative electrode. When the electrode is a negative electrode, the counter electrode is a positive electrode. Hereinafter, the positive electrode and the negative electrode used as the counter electrode of the above-mentioned electrodes will be described respectively.
[0096] (1-1) Negative electrode As the negative electrode used as the counter electrode, a negative electrode having a negative electrode active material layer can be used. As the negative electrode active material layer, a material layer containing at least a known active material (hereinafter sometimes referred to as “negative electrode active material”) can be used.
[0097] In the case of lithium ion secondary batteries, examples of negative electrode active materials include natural graphite, artificial graphite, difficult-graphitizable carbon, easy-graphitizable carbon, lithium, lithium alloys, silicon, silicon alloys, silicon oxide, tin, tin alloys, tin oxide, phosphorus, germanium, indium, copper oxide, antimony sulfide, titanium oxide, iron oxide, manganese oxide, cobalt oxide, nickel oxide, lead oxide, ruthenium oxide, tungsten oxide, and zinc oxide. In addition, LiVO2, Li2VO4, Li4Ti5O 12 The negative electrode active material may be used alone or in combination of two or more.
[0098] In the case of a sodium ion secondary battery, a negative electrode active material that does not contain lithium atoms and a negative electrode active material in which lithium atoms are replaced by sodium atoms in the negative electrode active material used in the above-mentioned lithium ion secondary battery can be used. It should be noted that when the negative electrode active material is lithium or a lithium alloy, and sodium or a sodium alloy, the current collector itself can be used as an electrode without using it. In addition, as other negative electrode active materials, potassium, magnesium, calcium, aluminum, zinc, etc. can be used.
[0099] The negative electrode active material layer contains the negative electrode active material, and may contain, for example, a binder, a conductive aid, etc. as necessary. The binder and the conductive aid used in the negative electrode active material layer may be the same as those described in the above section “C. Electrode”, and thus their description is omitted here.
[0100] (1-2) Positive electrode As the positive electrode used as the counter electrode, a positive electrode having a positive electrode active material layer can be used. As the positive electrode active material layer, a material layer containing at least a known active material (hereinafter sometimes referred to as “positive electrode active material”) can be used. Examples of the positive electrode active material include lithium transition metal composite oxides, lithium-containing transition metal phosphate compounds, lithium-containing silicate compounds, etc. The positive electrode active material may be used alone or in combination of two or more.
[0101] Examples of the transition metal of the above-mentioned lithium transition metal composite oxide include vanadium, titanium, chromium, manganese, iron, cobalt, nickel, copper, etc. Specific examples of the lithium transition metal composite oxide include lithium cobalt composite oxides such as LiCoO2, lithium nickel composite oxides such as LiNiO2, lithium manganese composite oxides such as LiMnO2, LiMn2O4, Li2MnO3, and substances in which a part of the transition metal atoms serving as the main body of these lithium transition metal composite oxides is replaced with other metals such as aluminum, titanium, vanadium, chromium, manganese, iron, cobalt, lithium, nickel, copper, zinc, magnesium, gallium, zirconium, etc. As for the lithium transition metal composite oxide in which a part of the transition metal atoms serving as the main body is replaced with other metals, as specific examples, for example, Li 1.1 Mn 1.8 Mg 0.1 O4、Li 1.1 Mn 1.85 Al 0.05 O4、LiNi 0.5 Co 0.2 Mn 0.3 O2、LiNi 0.8 Co 0.1 Mn 0.1 O2、LiNi 0.5 Mn 0.5 O2、LiNi 0.80 Co 0.17 Al 0.03 O2、LiNi 0.80 Co 0.15 Al 0.05 O2、Li(Ni 1 / 3 Co 1 / 3 Mn 1 / 3 )O2、LiNi 0.6 Co 0.2 Mn 0.2 O2、LiMn 1.8 Al 0.2 O4、LiNi 0.5 Mn 1.5 O4, Li2MnO3-LiMO2 (M=Co, Ni, or Mn), etc.
[0102] Examples of the transition metal in the above lithium-containing transition metal phosphate compound include vanadium, titanium, manganese, iron, cobalt, nickel, etc. Specific examples of the lithium-containing transition metal phosphate compound include iron phosphate compounds such as LiFePO4, LiMn x Fe 1-x PO4(0 < x < 1) and other iron phosphate compounds, iron sulfate compounds such as LiFeSO4F, cobalt phosphate compounds such as LiCoPO4, substances in which a part of the transition metal atoms that are the main body of these lithium transition metal phosphate compounds are replaced with other metals such as aluminum, titanium, vanadium, chromium, manganese, iron, cobalt, lithium, nickel, copper, zinc, magnesium, gallium, zirconium, niobium, etc., vanadium phosphate compounds such as Li3V2(PO4)3, etc.
[0103] Examples of the above lithium-containing silicate compound include Li2FeSiO4, etc.
[0104] The above positive electrode active material layer contains the above-mentioned well-known active material, and may also contain, for example, a binder, a conductive assistant, etc. as needed. Regarding the binder and the conductive assistant used in the above positive electrode active material layer, the same substances as those described in the above item "C. Electrode" can be used, and thus the description is omitted here.
[0105] (2) Electrolyte The above electrolyte is not particularly limited, and a well-known electrolyte can be used. Examples of the electrolyte include: a liquid electrolyte obtained by dissolving a supporting electrolyte in an organic solvent, a polymer gel electrolyte obtained by dissolving a supporting electrolyte in an organic solvent and gelling it with a polymer, a polymer electrolyte obtained by dispersing a supporting electrolyte in a polymer without an organic solvent, an inorganic solid electrolyte, etc. In addition, two or more of the above electrolytes can be used in combination. In the present disclosure, from the viewpoints of further increasing the discharge capacity and being easy to manufacture, the electrolyte is preferably a liquid electrolyte, a polymer electrolyte or an inorganic solid electrolyte, and more preferably a liquid electrolyte.
[0106] In the present disclosure, as a supporting electrolyte for a liquid electrolyte and a polymer gel electrolyte, in the case of a lithium-ion secondary battery, a conventionally well-known lithium salt can be used. Examples of the supporting electrolyte include: LiPF6, LiBF4, LiAsF6, LiCF3SO3, LiCF3CO2, LiN(CF3SO2)2, LiN(C2F5SO2)2, LiN(SO2F)2, LiC(CF3SO2)3, LiB(CF3SO3)4, LiB(C2O4)2, LiBF2(C2O4), LiSbF6, LiSiF5, LiSCN, LiClO4, LiCl, LiF, LiBr, LiI, LiAlF4, LiAlCl4, LiPO2F2, and their derivatives, etc. Among them, from the viewpoint of further increasing the discharge capacity, it is preferable to use one or more selected from LiPF6, LiBF4, LiClO4, LiAsF6, LiCF3SO3, LiN(CF3SO2)2, LiN(C2F5SO2)2, LiN(SO2F)2, derivatives of LiC(CF3SO2)3, LiCF3SO3, and derivatives of LiC(CF3SO2)3.
[0107] From the viewpoint of further increasing the discharge capacity, the content of the supporting electrolyte in the liquid electrolyte or the polymer gel electrolyte is preferably 0.5 mol / L to 7 mol / L, and more preferably 0.8 mol / L to 1.8 mol / L.
[0108] As a supporting electrolyte for a polymer electrolyte, in the case of a lithium-ion secondary battery, for example, LiN(CF3SO2)2, LiN(C2F5SO2)2, LiN(SO2F)2, LiC(CF3SO2)3, LiB(CF3SO3)4, LiB(C2O4)2 can be cited.
[0109] In the present disclosure, as an inorganic solid electrolyte, in the case of a lithium-ion secondary battery, for example, Li 1+x A x B 2-x (PO4)3 (A = Al, Ge, Sn, Hf, Zr, Sc or Y, B = Ti, Ge or Zn, 0 < x < 0.5), LiMPO4 (M = Mn, Fe, Co or Ni), Li3PO4 and other phosphate-based materials; Li3XO4 (X = As or V), Li 3+x A x B 1-x O4 (A = Si, Ge or Ti, B = P, As or V, 0 < x < 0.6), Li 4+x A x Si 1-xO4 (when A = B, Al, Ga, Cr or Fe, 0 < x < 0.4; when A = Ni or Co, 0 < x < 0.1), Li 4-3y Al y SiO4 (0 < y < 0.06), Li 4-2y Zn y GeO4 (0 < y < 0.25), LiAlO2, Li2BO4, Li4XO4 (X = Si, Ge or Ti), lithium titanates (LiTiO2, LiTi2O4, Li4TiO4, Li2TiO3, Li2Ti3O7, or Li4Ti5O 12 ) and other lithium composite oxides; compounds containing lithium and halogen such as LiBr, LiF, LiCl, LiPF6, LiBF4; compounds containing lithium and nitrogen such as LiPON, LiN(SO2CF3)2, LiN(SO2C2F5)2, Li3N, LiN(SO2C3F7)2; La 0.55 Li 0.35 TiO3 and other crystals with perovskite structure having lithium ion conductivity; Li7-La3Zr2O 13 and other crystals with garnet-type structure; glasses such as 50Li4SiO4·50Li3BO 33 , 90Li3BO3·10Li2SO4; lithium / sulfur-phosphorus compounds such as 70Li2S·30P2S5, 75Li2S·25P2S5, Li6PS5Cl, Li 9.54 Si 1.74 P 1.44 S 11.7 Cl 0.3 , Li6PS5P 1.44 C l3 Li 10 GeP2S 12 Li 3.25 Ge 0.25 P 0.75 S4 and other lithium / phosphorus-sulfide system crystals; lithium / phosphorus-sulfide system glasses such as 30Li2S·26B2S3·44LiI, 50Li2S·17P2S5·33LiBH, 50Li2S·50GeS2, 63Li2S·36SiS2·1Li3PO4, 57Li2S·38SiS2·5Li4SiO4, 70Li2S·50GeS2; Li7P3S 11 Li 3.25 P 0.95 S4, Li 10 GeP2S 12 Li 9.6 P3S 12 and Li 9.54 Si 1.74 P1.44 S 11.7 Cl 0.3 Glass ceramics, etc. It should be noted that the inorganic solid electrolyte may also be covered with a polymer gel electrolyte. In addition, when an inorganic solid electrolyte is used, a polymer gel electrolyte layer may be provided between the inorganic solid electrolyte layer and the electrode.
[0110] In the case of a sodium ion secondary battery, a supporting electrolyte in which lithium atoms in the above-mentioned lithium ion secondary battery are replaced with sodium atoms can be used.
[0111] In the present disclosure, as the organic solvent for liquid electrolyte and polymer gel electrolyte, the organic solvent commonly used for liquid electrolyte can be used. As the specific example of organic solvent, can enumerate: saturated cyclic carbonate compound, saturated cyclic ester compound, sulfoxide compound, sulfone compound, amide compound, saturated chain carbonate compound, chain ether compound, cyclic ether compound, saturated chain ester compound etc.. Wherein, from the viewpoint that relative dielectric constant is high and plays the effect of improving the dielectric constant of electrolyte and discharge capacity further increases, preferably saturated cyclic carbonate compound, saturated cyclic ester compound, sulfoxide compound, sulfone compound and amide compound, more preferably saturated cyclic carbonate compound. In addition, wherein, from the viewpoint that can reduce the viscosity of electrolyte, improve the mobility of electrolyte ions, make the battery characteristics such as output density excellent, preferably saturated chain carbonate compound, chain ether compound, cyclic ether compound and saturated chain ester compound, more preferably saturated chain carbonate compound.
[0112] Examples of the saturated cyclic carbonate compound include ethylene carbonate, fluoroethylene carbonate, 1,2-propylene carbonate, 1,3-propylene carbonate, 1,2-butylene carbonate, 1,3-butylene carbonate, and 1,1-dimethylethylene carbonate.
[0113] Examples of the saturated cyclic ester compound include γ-butyrolactone, γ-valerolactone, γ-caprolactone, δ-caprolactone, and δ-octanolactone.
[0114] Examples of the sulfoxide compound include dimethyl sulfoxide, diethyl sulfoxide, dipropyl sulfoxide, diphenyl sulfoxide, and thiophene.
[0115] Examples of the sulfone compound include dimethyl sulfone, diethyl sulfone, dipropyl sulfone, diphenyl sulfone, sulfolane (also called tetramethylene sulfone), 3-methyl sulfolane, 3,4-dimethyl sulfolane, 3,4-diphenylmethyl sulfolane, sulfolene, 3-methyl sulfolene, 3-ethyl sulfolene, 3-bromomethyl sulfolene, etc. Among them, sulfolane and tetramethyl sulfolene are preferred from the viewpoint of further increasing the discharge capacity.
[0116] Examples of the amide compound include N-methylpyrrolidone, dimethylformamide, and dimethylacetamide.
[0117] Examples of the saturated chain carbonate compound include dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, ethyl butyl carbonate, methyl tert-butyl carbonate, diisopropyl carbonate, tert-butylpropyl carbonate, and the like.
[0118] Examples of the chain ether compounds and cyclic ether compounds include dimethoxyethane, ethoxymethoxyethane, diethoxyethane, tetrahydrofuran, dioxolane, dimethoxyethane, alkane, 1,2-bis(methoxycarbonyloxy)ethane, 1,2-bis(ethoxycarbonyloxy)ethane, 1,2-bis(ethoxycarbonyloxy)propane, ethylene glycol bis(trifluoroethyl)ether, propylene glycol bis(trifluoroethyl)ether, ethylene glycol bis(trifluoromethyl)ether, diethylene glycol bis(trifluoroethyl)ether, glycol diethers, etc. Among them, dioxolane is preferred from the viewpoint of further increasing the discharge capacity.
[0119] Examples of the saturated chain ester compounds include monoester compounds and diester compounds having a total carbon number of 2 to 8 in the molecule. Specific examples of the saturated chain ester compounds include methyl formate, ethyl formate, methyl acetate, ethyl acetate, propyl acetate, isobutyl acetate, butyl acetate, methyl propionate, ethyl propionate, methyl butyrate, methyl isobutyrate, methyl trimethylacetate, ethyl trimethylacetate, methyl malonate, ethyl malonate, methyl succinate, ethyl succinate, methyl 3-methoxypropionate, ethyl 3-methoxypropionate, ethylene glycol diacetyl, propylene glycol diacetyl, etc. Among them, methyl formate, ethyl formate, methyl acetate, ethyl acetate, propyl acetate, isobutyl acetate, butyl acetate, methyl propionate, and ethyl propionate are preferred from the viewpoint of further increasing the discharge capacity.
[0120] Examples of other organic solvents that can be used to prepare the electrolyte include acetonitrile, propionitrile, nitromethane or derivatives thereof, and various ionic liquids.
[0121] Examples of polymers used in polymer gel electrolytes include polyethylene oxide, polypropylene oxide, polyvinyl chloride, polyacrylonitrile, polymethyl methacrylate, polyethylene, polyvinylidene fluoride, polyhexafluoropropylene, etc. There are no particular restrictions on the ratio of polymers in the polymer gel electrolyte and the gelation method, and the ratio and gelation method known in the art can be used.
[0122] Examples of polymers used in polymer electrolytes include polyethylene oxide, polypropylene oxide, polystyrene sulfonic acid, and polyvinylidene fluoride. There are no particular restrictions on the ratio of polymers in the polymer electrolyte and the method of compounding, and any ratio or compounding method known in the art can be used.
[0123] In order to improve battery life, improve safety, etc., the electrolyte may contain, for example, electrode film forming agents, antioxidants, flame retardants, overcharge protection agents and other known additives. From the viewpoint of further increasing the discharge capacity, the content of other additives is generally 0.01 to 10 parts by mass, preferably 0.1 to 5 parts by mass, relative to 100 parts by mass of the electrolyte as a whole.
[0124] (3) Diaphragm As the above-mentioned separator, as long as lithium ions are allowed to penetrate and contact between the positive electrode and the negative electrode is prevented, there is no particular limitation, for example, a microporous film or nonwoven fabric of a polymer can be used. As an example of a film, a film formed by the following substances can be cited: a polymer compound or its derivatives based on polyethers such as polyethylene, polypropylene, polyvinylidene fluoride, polyvinylidene chloride, polyacrylonitrile, polyacrylamide, polytetrafluoroethylene, polysulfone, polyether sulfone, polycarbonate, polyamide, polyimide, polyethylene oxide or polypropylene oxide, carboxymethyl cellulose or hydroxypropyl cellulose, etc., a polymer compound based on poly (meth) acrylic acid and its various esters, etc., their copolymers or mixtures, etc. These films can be coated with ceramic materials such as aluminum oxide or silicon dioxide, magnesium oxide, aromatic polyamide resin, or polyvinylidene fluoride.
[0125] These films can be used alone, or the films can be overlapped and used as multilayer films. In addition, various additives can be used in these films, and their types and contents are not particularly limited. In these films, from the viewpoint that the discharge capacity of the secondary battery is further increased, the film preferably composed of polyethylene, polypropylene, polyvinylidene fluoride or polysulfone is considered. In addition, when the electrolyte is a polymer electrolyte or an inorganic solid electrolyte, a separator may not be included.
[0126] (4) Others In the present disclosure, the shape of the battery is not particularly limited, and may be various shapes such as a coin shape, a cylinder shape, a square shape, a laminate shape, etc.
[0127] As the outer packaging component of the battery, a laminated film or a metal container can be used. The thickness of the outer packaging component is usually less than 0.5 mm, preferably less than 0.3 mm. As the shape of the outer packaging component, flat (thin), square, cylindrical, coin-shaped, button-shaped, etc. can be mentioned.
[0128] As the laminated film, a multilayer film having a metal layer between resin films can be used. In order to reduce weight, the metal layer is preferably aluminum foil or aluminum alloy foil. The resin film can be made of a polymer material such as polypropylene, polyethylene, nylon, polyethylene terephthalate, etc. The laminated film can be sealed by hot melting and formed into the shape of an exterior component. The metal container can be formed of, for example, stainless steel, aluminum or an aluminum alloy. As the aluminum alloy, an alloy containing elements such as magnesium, zinc, and silicon is preferred. In aluminum or an aluminum alloy, by making the content of transition metals such as iron, copper, nickel, and chromium less than 1% by mass, the long-term reliability and heat dissipation in a high temperature environment can be greatly improved.
[0129] 3. Battery The battery disclosed herein may be either a primary battery or a secondary battery, but is preferably a secondary battery because it is useful as a battery for vehicle use.
[0130] E. Others In the present disclosure, the following embodiments can be cited. [1] A sulfur-containing material characterized in that it contains a sulfur-modified compound, the total sulfur content is 50% by mass or more, and the ratio (A / B) of the maximum peak intensity (A) in the range of a diffraction angle (2θ) of 23.0° to 23.4° to the maximum peak intensity (B) in the range of a diffraction angle (2θ) of 24.8° to 25.2° obtained by powder X-ray diffraction using CuKα rays is 1.5 or less (A / B≤1.5). [2] The sulfur-containing material according to [1], wherein the sulfur-modified compound is a sulfur-modified acrylic compound. [3] A sulfur-containing battery material characterized in that it contains a sulfur-modified compound, the total sulfur content is 50% by mass or more, and the ratio (A / B) of the maximum peak intensity (A) in the range of a diffraction angle (2θ) of 23.0° to 23.4° to the maximum peak intensity (B) in the range of a diffraction angle (2θ) of 24.8° to 25.2° obtained by powder X-ray diffraction using CuKα rays is 1.5 or less (A / B≤1.5). [4] The sulfur-containing battery material according to [3], wherein the sulfur-modified compound is a sulfur-modified acrylic compound. [5] An electrode having an electrode layer, wherein the electrode layer contains the sulfur-containing material according to [1] or [2] or the sulfur-containing battery material according to [3] or [4]. [6] A battery comprising the electrode described in [5]. [7] The battery according to [6], wherein the electrode is a positive electrode. [8] The battery according to [7], wherein the negative electrode is lithium.
[0131] The present disclosure is not limited to the above-mentioned embodiments. The above-mentioned embodiments are merely illustrative, and all embodiments having substantially the same configuration as the technical concept described in the claims and having the same functions and effects are included in the technical scope of the present disclosure. Example
[0132] The present disclosure is described in more detail below by way of examples and comparative examples. However, the present disclosure is not limited by the following examples and the like. It should be noted that, unless otherwise specified, "parts" or "%" in the examples are based on mass.
[0133] [Example 1] Preparation of sulfur-containing material A First, a heating process is performed according to the method of the manufacturing example of Japanese Patent Publication No. 2013-054957. That is, 20 g of a mixture (hereinafter sometimes referred to as "raw material PAN mixture") of 10 parts by mass of polyacrylonitrile powder (made by Sigma-Aldrich, with an average particle size of 200 μm) and 30 parts by mass of elemental sulfur (made by Sigma-Aldrich, with an average particle size of 200 μm) is placed in a bottomed cylindrical glass tube with an outer diameter of 45 mm and a length of 120 mm, and a silicon plug having a gas inlet pipe and a gas outlet pipe is installed at the opening of the glass tube. After the air inside the glass tube is replaced with nitrogen, a crucible-type electric furnace is inserted into the lower part of the glass tube, and heated at 400°C for 1 hour, while removing the generated hydrogen sulfide by introducing nitrogen from the gas inlet pipe, to obtain a heat-treated product 1. It should be noted that sulfur vapor condenses and refluxes at the upper part or the cover of the glass tube. The obtained heat-treated product 1 was placed in a glass tube oven at 260° C. and heated for 3.0 hours under the condition of reduced pressure to 20 hPa to remove elemental sulfur, thereby obtaining a heat-treated product 2. The total sulfur content of the heat-treated product 2 was 49% by mass, and the content of elemental sulfur contained in the heat-treated product 2 was 0% by mass. Then, a mechanochemical treatment step was performed. 30 parts by mass of elemental sulfur (manufactured by Sigma-Aldrich, with an average particle size of 200 μm) was added to 100 parts by mass of the heat-treated product 2 so as to obtain a peak intensity ratio (A / B) of powder X-ray diffraction shown in Table 1, thereby obtaining a heat-treated product 3, and the heat-treated product 3 was mechanochemically treated in an argon atmosphere using a planetary ball mill (manufactured by Fritsch, P-7 Classic Line) at a rotation speed of 1600 rpm for 300 minutes to obtain a sulfur-containing material A. The Raman spectrum of sulfur-containing material A is shown in Figure 1 The ratio of the peak intensity A1 to the peak intensity B1 (A1 / B1) is found to be 110.8 / 56.1=1.98.
[0134] [Example 2] Preparation of sulfur-containing material B Heat-treated product 4 was obtained in the same manner as in Example 1 except that the reduced-pressure heating time for heat-treated product 1 was changed to 1.5 hours. The total sulfur content of the heat-treated product 4 was 60% by mass, and the content of elemental sulfur contained in the heat-treated product 4 was 11% by mass. Then, the heat-treated product 4 was subjected to mechanochemical treatment in an argon atmosphere using a planetary ball mill (manufactured by Fritsch, P-7 Classic Line) at a rotation speed of 1600 rpm for a treatment time of 300 minutes, thereby obtaining a sulfur-containing material B.
[0135] [Example 3] Production of sulfur-containing material C The same operation as in Example 1 was performed to obtain a heat-treated product 2, and then 11 parts by mass of elemental sulfur (manufactured by Sigma-Aldrich, with an average particle size of 200 μm) was added to 100 parts by mass of the heat-treated product 2 to obtain a heat-treated product 5. The heat-treated product 5 was mechanochemically treated in an argon atmosphere using a planetary ball mill (manufactured by Fritsch, P-7Classic Line) at a rotation speed of 1600 rpm for 100 minutes to obtain a sulfur-containing material C.
[0136] [Comparative Example 1] Production of Sulfur-Containing Material a The heat-treated product 1 was placed in a glass tube oven at 260° C. and heated for 3.0 hours under the condition of reduced pressure to 20 hPa to remove elemental sulfur, thereby obtaining a sulfur-containing material a.
[0137] [Comparative Example 2] Production of sulfur-containing material b A sulfur-containing material b was obtained in the same manner as in Comparative Example 1 except that the reduced-pressure heating time for the heat-treated product 1 was changed to 1.5 hours.
[0138] [Comparative Example 3] Production of Sulfur-Containing Material c The same operation as in Example 1 was performed to obtain a heat-treated product 2, and then 160 parts by weight of elemental sulfur (manufactured by Sigma-Aldrich, with an average particle size of 200 μm) was added to 100 parts by weight of the heat-treated product 2 in such a manner as to obtain a peak intensity ratio (A / B) of powder X-ray diffraction as shown in Table 1, thereby obtaining a heat-treated product 6. The heat-treated product 6 was mechanochemically treated in an argon atmosphere using a planetary ball mill (manufactured by Fritsch, P-7 Classic Line) at a rotation speed of 2000 rpm for 400 minutes to obtain a sulfur-containing material c.
[0139] [Comparative Example 4] Production of sulfur-containing material d A sulfur-containing material d was obtained in the same manner as in Comparative Example 1 except that the reduced-pressure heating time for the heat-treated product 1 was changed to 2.0 hours.
[0140] [Total sulfur content] The total sulfur content (mass %) in the sulfur-containing materials obtained in the examples and comparative examples was calculated based on the analysis results using a CHNS analyzer (Elementar Analysensysteme GmbH, model: varioMICRO cube) capable of analyzing sulfur and oxygen. The combustion tube temperature was 1150°C, the reduction tube temperature was 850°C, and a tin boat was used as the sample container. The results are shown in Tables 1 to 3.
[0141] [Peak intensity ratio of powder X-ray diffraction] The sulfur-containing materials obtained in the examples and comparative examples were subjected to X-ray diffraction analysis using a powder X-ray diffractometer (Ultima IV, manufactured by RIKEN Co., Ltd.). The measurement conditions were set as follows: CuKα radiation, voltage: 40 kV, current: 40 mA, scanning speed: 0.5° / min, sampling: 0.02°, cumulative number: 1, and diffraction angle (2θ): 10° to 40°. The ratio of the maximum peak intensity (A) in the diffraction angle (2θ) range of 22.8° to 23.2° and the maximum peak intensity (B) in the diffraction angle (2θ) range of 24.8° to 25.2° obtained from the diffraction pattern obtained by X-ray diffraction was calculated. The results are shown in Tables 1 to 3.
[0142] [Ignition test] 4 g of the sulfur-containing material obtained in the examples and comparative examples were weighed and placed on a heat-insulating plate in a hemispherical shape. An ignition device adjusted to a diffusion flame length of about 7 mm was used to allow the flame to contact the sulfur-containing material for 10 seconds, so that the contact area between the flame and the sulfur-containing material was 2 cm 2 , the contact angle is about 30°. At this time, the case where no ignition or combustion occurred after contact for 10 seconds was evaluated as "no ignition", and the case where ignition or combustion occurred was evaluated as "ignition". The material that did not ignite (not ignited) can be judged to have high flame retardancy. The results are shown in Tables 1 to 3.
[0143] [Battery evaluation using liquid electrolyte] Secondary batteries were produced using the sulfur-containing materials obtained in Examples and Comparative Examples.
[0144] (1) Preparation of positive electrode A composition for forming an electrode layer was prepared by mixing 90.0 parts by mass of a sulfur-containing material as an active material for a positive electrode active material layer, 5.0 parts by mass of acetylene black (manufactured by Denka Co., Ltd.) as a conductive aid, 3.0 parts by mass of styrene-butadiene rubber (aqueous dispersion, manufactured by Zeon Co., Ltd.) as a binder, 2.0 parts by mass of sodium carboxymethyl cellulose (manufactured by Daicel Fine Chem Co., Ltd.), and 120 parts by mass of water as a solvent using a rotation / revolution stirrer. The electrode layer-forming composition was applied to a carbon-coated aluminum foil (thickness 20 μm) as a current collector by a doctor blade method and dried at 90° C. for 1 hour. The electrode was then cut into a predetermined size and vacuum dried at 130° C. for 2 hours to prepare a disk-shaped positive electrode.
[0145] (2) Preparation of negative electrode A 500 μm thick lithium metal was cut into a predetermined size to prepare a disk-shaped negative electrode.
[0146] (3) Preparation of electrolyte In a mixed solvent consisting of 50 volume % of fluoroethylene carbonate and 50 volume % of diethyl carbonate, LiPF6 was dissolved at a concentration of 1.0 mol / L to prepare an electrolyte solution 1. In a mixed solvent consisting of 50 volume % of dimethoxyethane and 50 volume % of dioxolane, LiN(CF3SO2)2 was dissolved at a concentration of 1.0 mol / L to prepare an electrolyte solution 2.
[0147] (4) Battery production The glass filter as a separator was sandwiched between the previously prepared positive and negative electrodes and held in the housing. Then, the previously prepared electrolyte solution 1 was injected into the housing, and the housing was sealed and sealed to produce a secondary battery (coin-shaped with a diameter of 20 mm and a thickness of 3.2 mm). It should be noted that the production sequence of "(4) Production of Batteries" was carried out in an atmosphere with a dew point of -70°C. Secondary batteries were prepared in the same manner as above except that the electrolyte solution 1 was changed to the electrolyte solution 2.
[0148] (5) Evaluation method The secondary battery prepared above was placed in a thermostatic chamber at 25°C, the charge termination voltage was set to 3.0V, the discharge termination voltage was set to 1.0V, and the charge and discharge were performed for 100 cycles at a charge rate of 0.1C and a discharge rate of 0.1C, and the discharge capacity (mAh / g) of the 10th cycle and the 100th cycle was measured. The results of the discharge capacity (mAh / g) of the 10th cycle are shown in Tables 1 to 3. It should be noted that in the present disclosure, the "g" in the discharge capacity (mAh / g) represents the mass of the active material in the positive electrode active material layer. In addition, the ratio of the discharge capacity at the 100th cycle to the discharge capacity at the 10th cycle was defined as the capacity retention rate (%), and the cycle characteristics were evaluated. The results are shown in Tables 1 to 3.
[0149] [Battery evaluation using solid electrolyte] (1) Battery production 50.0 parts by mass of a sulfur-containing material as an electrode active material, 5.0 parts by mass of acetylene black (manufactured by Denka) as a conductive aid, and 45.0 parts by mass of LPS (Li2S:P2S5=75:25 (molar ratio)) as a solid electrolyte were mixed using a ball mill and molded by pressing to prepare a circular positive electrode active material layer with a diameter of 10 mm. Next, the LPS was molded by a press process to prepare a circular solid electrolyte layer with a diameter of 10 mm. Then, the stack was stacked in the order of SUS foil / positive electrode active material layer / solid electrolyte layer / indium-lithium alloy / SUS foil, and the stack was pressed under a load of 20 kN and sealed in a solid-state battery evaluation unit (manufactured by Hohsen Co., Ltd., model KP-SolidCell) to make solid-state secondary batteries. It should be noted that the production sequence of "(1) battery production" was carried out under an argon atmosphere. (2) Evaluation method The all-solid secondary battery prepared above was placed in a thermostatic chamber at 60°C, the charge termination voltage was set to 2.38V, the discharge termination voltage was set to 0.38V, and 50 cycles of charge and discharge were performed at a charge rate of 0.05C and a discharge rate of 0.05C, and the discharge capacity (mAh / g) of the 5th cycle and the 50th cycle were measured. The results of the discharge capacity (mAh / g) of the 5th cycle are shown in Tables 1 to 3. It should be noted that in the present disclosure, the "g" in the discharge capacity (mAh / g) represents the mass of the active material in the positive electrode active material layer. In addition, the ratio of the discharge capacity at the 50th cycle to the discharge capacity at the 5th cycle was defined as the capacity retention rate (%), and the cycle characteristics were evaluated. The results are shown in Tables 1 to 3.
[0150] [Table 1]
[0151] [Table 2]
[0152] [Table 3]
[0153] The results of powder X-ray diffraction of sulfur-containing material A are as follows: Figure 2The peak intensity ratio (A / B) of the powder X-ray diffraction of the sulfur-containing material A was found to be 390 / 573.3=0.68, confirming that the amount of elemental sulfur contained in the sulfur-containing material A was so small that the discharge capacity and cycle characteristics did not decrease. The powder X-ray diffraction results of sulfur-containing material b are as follows: Figure 3 The peak intensity ratio (A / B) of the powder X-ray diffraction was found to be 930.0 / 414.0=2.25, which confirmed that the elemental sulfur contained in the sulfur-containing material b was such that the discharge capacity and cycle characteristics were reduced. The above results show that the sulfur-containing material of the embodiment has high flame retardancy, and thus can improve the safety of the battery. It is also known that the battery using the sulfur-containing material of the embodiment has a large discharge capacity. It is also known that the battery using the sulfur-containing material of the embodiment has an improved capacity retention rate, and thus has excellent cycle characteristics.
Claims
1. A sulfur-containing material, characterized in that: Contains sulfur-modified compounds, The total sulfur content is 50% by mass or more, The ratio A / B of the maximum peak intensity A in the diffraction angle 2θ range of 23.0° to 23.4° and the maximum peak intensity B in the diffraction angle 2θ range of 24.8° to 25.2° obtained by powder X-ray diffraction using CuKα rays is less than 1.5, that is, A / B≤1.
5.
2. The sulfur-containing material according to claim 1, characterized in that: The sulfur-modified compound is a sulfur-modified acrylic compound.
3. A sulfur-containing battery material, characterized in that: Contains sulfur-modified compounds, The total sulfur content is 50% by mass or more, The ratio A / B of the maximum peak intensity A in the diffraction angle 2θ range of 23.0° to 23.4° and the maximum peak intensity B in the diffraction angle 2θ range of 24.8° to 25.2° obtained by powder X-ray diffraction using CuKα rays is less than 1.5, that is, A / B≤1.
5.
4. The sulfur-containing battery material according to claim 3, characterized in that: The sulfur-modified compound is a sulfur-modified acrylic compound. 5 . An electrode comprising an electrode layer, wherein the electrode layer contains the sulfur-containing material according to claim 1 . A battery comprising the electrode according to claim 5.
7. The battery according to claim 6, wherein The electrode is a positive electrode.
8. The battery according to claim 7, wherein The negative electrode is lithium.
Citation Information
Patent Citations
Method for manufacturing positive electrode for nonaqueous electrolyte secondary battery, positive electrode for nonaqueous electrolyte secondary battery, and nonaqueous electrolyte secondary battery
JP2013054957A
Device for continuously manufacturing organic sulfur-based anode material for secondary battery
JP2014022123A
Method of manufacturing electrode for non-aqueous electrolyte secondary battery
JP2022065974A
Sulfur-modified polyacrylonitrile, manufacturing method therefor, and application thereof
WO2010044437A1
Cited By
Organic-inorganic compound thick electrode and preparation method and application thereof
CN121601578A
An organic-inorganic compound thick electrode, a preparation method and application thereof
CN121601578B